POPULASI POHON JENIS DIPTEROCARPACEAE DITIGA TIPE HUTAN PAMAH KALIMANTAN - Herwint Simbolon (BERITA BIOLOGI, 2008)
Data of Dipterocarpaceae species have been extracted from 8 studied plots of 1-ha each, distributed in three types of natural forest in Kalimantan (those were 4 plots in mixed dipterocarps forest, 2 plots in peat swamp forest and 2 plots in heath forest types) for further population analysis. Number of Dipterocarpaceae species in mixed dipterocarps forest type was higher than of in two other forest types, however mean number of individual per species was higher in peat swamp and heath forest types than of in mixed dipterocarps forest type. Some of Dipterocarpaceae species are adapted to heath and peat swamp forest type conditions indicated by the number and distribution of population of the species in both forest types. The higher the population number of juvenile trees 5-10 cm in diameter, the lower population number of mature trees of diameter 50cm up, indicated the higher tree population the higher mortality rate. However, survivorship of tree will higher as the tree diameter higher. Survivorship of trees in mixed dipterocarp forest is higher than of in peat swamp and heath forest types.